A new species of Hoplosaenidea Laboissiere, 1933 from Malaysia (Coleoptera: Chrysomelidae: Galerucinae) - Mohamedsaid, Mohamed S. (Zootaxa, 2009)
Recently, the author described two species of the genus Hoplosaenidea Laboissiere, 1933 (Coleoptera: Chrysomelidae: Galerucinae) where the male having a peculiar secondary sexual characters: clypeus excavated, furnished with projections, and the antennal first segment large, broadened, excavated and spined at apex. The two species are H. takizawai Mohamedsaid, 2001 (Fig. 5) and H. singaporensis Mohamedsaid, 2002 (Fig. 6) described from Bali and Singapore, respectively. The presence of secondary sexual characters in males is most prevalent in the chrysomelid beetles of the subfamily Galerucinae (Mohamedsaid 2004b).